A synthetic biology approach to transform Yarrowia lipolytica into a competitive biotechnological producer of β‐carotene - Larroude, Macarena; Celinska, Ewelina; Back, Alexandre; Thomas, Stephan; Nicaud, Jean‐Marc; Ledesma‐Amaro, Rodrigo (Biotechnology and bioengineering, 2018)
The increasing market demands of β‐carotene as colorant, antioxidant and vitamin precursor, requires novel biotechnological production platforms. Yarrowia lipolytica, is an industrial organism unable to naturally synthesize carotenoids but with the ability to produce high amounts of the precursor Acetyl‐CoA. We first found that a lipid overproducer strain was capable of producing more β‐carotene than a wild type after expressing the heterologous pathway. Thereafter, we developed a combinatorial synthetic biology approach base on Golden Gate DNA assembly to screen the optimum promoter‐gene pairs for each transcriptional unit expressed. The best strain reached a production titer of 1.5 g/L and a maximum yield of 0.048 g/g of glucose in flask. β‐carotene production was further increased in controlled conditions using a fed‐batch fermentation. A total production of β‐carotene of 6.5 g/L and 90 mg/g DCW with a concomitant production of 42.6 g/L of lipids was achieved. Such high titers suggest that engineered Y. lipolytica is a competitive producer organism of β‐carotene. In this work the yeast Yarrowia lipolytica is engineered using synthetic biology techniques in order to become a producer of high amounts of the high value compound, beta‐carotene. The combination of multi‐copy integration and random selection of promoters, using Golden Gate based approach, further increased production, reaching production levels higher than 6 g/L.